Online parking system : parking management and monitoring data - Mashuri, Nur Aina Syasya; Nordin, Siti Aminah; Hasan, Khairul Kamarudin; Abd Hamid, Fatimah Khairiah (UiTM Cawangan Johor Kampus Pasir Gudang, 2025)
Technology has greatly improved our lives, but parking remains a common problem. Many parking areas are poorly managed, causing congestion and frustration as drivers waste time searching for open spaces, especially in crowded areas. This project presents the design and simulation of an Online Parking System: Parking Management and Monitoring Data aims to create a mobile app that helps users find available parking spots easily. The app provides real-time updates on parking availability and locations, saving time and reducing stress. The system uses Arduino-based sensors and devices, including a Proximity Sensor, RFID Reader, and Relay Module. It’s equipped with a Wi-Fi module to enable remote monitoring and control, making it an IoT solution. The Proximity Sensor detects whether a parking spot is occupied or empty, and this information is sent to the app via the ESP32 Wi-Fi module. The mobile app allows users to track and locate parking spots in real time, offering a simple and effective way to manage parking.